Replication fidelity in the mircroevolution of mycobacteria - Ditse, Zanele (Division of Medical Biochemistry, 2015)
This thesis aimed to elucidate the structure-function relationships determining the differential fidelities of the dnaE1- and dnaE2-encoded mycobacterial PolIIIÎ± subunits under conditions of genotoxic stress. To this end, the role in DnaE1 intrinsic fidelity of highly conserved PHP domain residues was explored by site-directed replacement of targeted amino acids, resulting in a panel of Mycobacterium smegmatis mutants carrying selected dnaE1 alleles. A complementary approach investigated the contribution of the mycobacterial proofreading DnaQ subunit homolog to the maintenance of DnaE1-dependent replicative fidelity by generating a targeted dnaQ knockout mutant. The third component of this study focused on the inferred role of a highly-conserved N-terminal extension and C-terminal pentapeptide motif in the function of the alternative, error-prone DNA PolIIIÎ± subunit, DnaE2.